Promoting local development The BIDANI experience. - Garcia, L. O.; Africa, L. S. (2003)
The paper presented the historical highlights, features, key processes and achievements of BIDANI which have made it a unique and distinct * "nutrition-in-development" program of universities and colleges, addressing the malnutrition problem in the country through capacity building of Local Government Units. BIDANI is an integrated development approach with nutrition improvement as its ultimate goal. The achievements and lessons learned will help policy makers and planners at the national and local level to support development efforts of academic institutions in partnership with local government units in improving the general well-being of the poor.
Keywords: Barangay Integrated Development Approach for Nutrition Improvement (BIDANI); Local development